EARLY POST-OPERATIVE PERINEAL WOUND COMPLICATIONS IN PATIENTS UNDERGOING EXTRA LEVATOR ABDOMINOPERINEAL EXCISION, A RETROSPECTIVE STUDY AT DEPARTMENT OF SURGICAL ONCOLOGY - Aun Jamal (Army Medical College Rawalpindi, 2020)
Objective: To emphasize on the early wound complications of the above-mentioned procedure.